Association between socioeconomic position and tuberculosis in a large population-based study in rural Malawi. - Anna Odone; Amelia C Crampin; Venance Mwinuka; Simon Malema; J Nimrod Mwaungulu; Lumbani Munthali; Judith R Glynn (PLoS ONE, 2013)
SETTING:There is increasing interest in social structural interventions for tuberculosis. The association between poverty and tuberculosis is well established in many settings, but less clear in rural Africa. In Karonga District, Malawi, we found an association between higher socioeconomic status and tuberculosis from 1986-1996, independent of HIV status and other factors. OBJECTIVE:To investigate the relationship in the same area in 1997-2010. DESIGN:All adults in the district with new laboratory-confirmed tuberculosis were included. They were compared with community controls, selected concurrently and frequency-matched for age, sex and area. RESULTS:1707 cases and 2678 controls were interviewed (response rates >95%). The odds of TB were increased in those working in the cash compared to subsistence economy (p<0.001), and with better housing (p-trend=0.006), but decreased with increased asset ownership (p-trend=0.003). The associations with occupation and housing were partly mediated by HIV status, but remained significant. CONCLUSION:Different socioeconomic measures capture different pathways of the association between socioeconomic status and tuberculosis. Subsistence farmers may be relatively unexposed whereas those in the cash economy travel more, and may be more likely to come forward for diagnosis. In this setting "better houses" may be less well ventilated and residents may spend more time indoors.